QuEChERS and C18 as solid phase extraction sorbent - ultra-high performance liquid chromatography -ultraviolet-visible method for determination of parabens in cosmetics products - Ngoc-Van Thi Nguyen (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
Concerns are growing about human exposure to endocrine-disrupting chemicals (EDCs), especially during the preadolescent development stage. Parabens are prevalent EDCs widely used as additives in cosmetics. So, the determination of parabens in such products is important. In this study, we developed a reliable and sensitive method to determine simultaneously nine common parabens (methylparaben, ethylparaben, phenylparaben, benzylparaben, penthylparaben, and two groups of isomeric compounds include propylparaben, isopropyl paraben, and butylparaben, isobutylparaben) in cosmetics products. The QuEChERS and solid-phase extraction techniques are used for extraction parabens from non-surfactant cosmetics (perfume, mouth wash solution) and surfactant cosmetics (shampoo, cream, gel), respectively and quantified by using ultra-performance liquid chromatography coupled with the ultraviolet-visible detector. All nine compounds showed good linearity with regression coefficients predominantly above 0.990. The LOD and LOQ of parabens were 0.07 µg/mL; 0.2 µg/mL, respectively. The recoveries ranged from 80 to 110% with the relative standard deviations below 8%. The developed method was successfully applied to determine parabens in various commercial cosmetic products from a local supermarket and the total parabens concentrations are in a wide-ranged from 2.0 to 1270 mg/kg.